Population Mobility and Efficiency in the Provision of Regional Public Goods - David A. Vardy (Queen's University, Department of Economics, 1972)
The purpose of the present paper is to extend the analysis of public goods to situations where population is variable. The focus of the analysis will be a system of local governments, or a federation, where population movement is important and where boundary spillovers of benefits from local public goods may be generated. The paper will develop a simple model of local public good provision, and this model will be used to derive effeciency conditions for population movement between regions and for optimal production of public goods. A behavioural model of free migration will be presented to determine whether free migration of people between fiscal regions will lead to efficiency in locational choice. The general result that will be established is that the free market does not lead to an optimal allocation of population among fiscal regions.
Keywords: 330